The sensory worlds of ancient Egypt - Parkinson, RB (Routledge, 2019)
An overview is provided of ancient Egyptian perceptions of the various senses, and also of environments, in order to suggest possible approaches for modelling ancient sensations. A more detailed case study considers the sensory aspects, including performance, of literary texts from 1938–1755 bce and the implications of these for modern interpretation. Overall, the surviving data is limited to predominantly elite spheres, but it includes material, visual and textual cultures which can complement each other to enable an integrated analysis of the lived sensations of ancient Egyptians.